Africa's Pulse, No. 14, October 2016 - World Bank Group (World Bank, Washington, DC, 2016)
After slowing to 3 percent in 2015, economic growth in Sub-Saharan Africa is projected to fall to 1.6 percent in 2016, the lowest level in over two decades. Low commodity prices and tight financial conditions, exacerbated by domestic headwinds from policy uncertainty, droughts, and political and security concerns, continued to weigh on activity across the region. The overall slowdown in Sub-Saharan Africa's growth reflects economic deterioration in the region's largest economies. Economic performance was notably weak across oil exporters. At the same time, in about a quarter of the countries, economic growth is showing signs of resilience. Indeed, the pattern of growth across countries is far from homogeneous, suggesting that Sub- Saharan Africa is growing at diverging speeds. While many countries are registering a sharp slippage in economic growth, some countries—Ethiopia, Rwanda, and Tanzania—are continuing to post annual average growth rates of over 6 percent, exceeding the top tercile of the regional distribution; and several other countries—including Côte d'Ivoire and Senegal—have moved into the top tercile of performers. The "established" and "improved" performers tend to have stronger quality of monetary and fiscal policies, better business regulatory environment, more diverse structure of exports, and more effective public institutions.